Loss of form vision impairs spatial imagery - Occelli, Valeria; Lin, Jonathan B.; Lacey, Simon A.; Sathian, Krish (Frontiers in Human Neuroscience, 2014)
Previous studies have reported inconsistent results when comparing spatial imagery performance in the blind and the sighted, with some, but not all, studies demonstrating deficits in the blind. Here, we investigated the effect of visual status and individual preferences (“cognitive style”) on performance of a spatial imagery task. Participants with blindness resulting in the loss of form vision at or after age 6, and age- and gender-matched sighted participants, performed a spatial imagery task requiring memorization of a 4 × 4 lettered matrix and subsequent mental construction of shapes within the matrix from four-letter auditory cues. They also completed the Santa Barbara Sense of Direction Scale (SBSoDS) and a self-evaluation of cognitive style. The sighted participants also completed the Object-Spatial Imagery and Verbal Questionnaire (OSIVQ). Visual status affected performance on the spatial imagery task: the blind performed significantly worse than the sighted, independently of the age at which form vision was completely lost. Visual status did not affect the distribution of preferences based on self-reported cognitive style. Across all participants, self-reported verbalizer scores were significantly negatively correlated with accuracy on the spatial imagery task. There was a positive correlation between the SBSoDS score and accuracy on the spatial imagery task, across all participants, indicating that a better sense of direction is related to a more proficient spatial representation and that the imagery task indexes ecologically relevant spatial abilities. Moreover, the older the participants were, the worse their performance was, indicating a detrimental effect of age on spatial imagery performance. Thus, spatial skills represent an important target for rehabilitative approaches to visual impairment, and individual differences, which can modulate performance, should be taken into account in such approaches.